2012
DOI: 10.1002/chem.201101925
|View full text |Cite
|
Sign up to set email alerts
|

Designer Ionic Liquid Crystals Based on Congruently Shaped Guanidinium Sulfonates

Abstract: Ionic liquid crystals are mesogenic compounds that consist of cations and anions, usually rod-like cations and spherical anions. Herein we report a new method for the synthesis of ionic liquid crystals by using cations and anions of the same molecular shape with oppositely charged head groups. Thus, 4-alkoxyphenylpentamethylguanidinium 4-alkoxyphenylsulfonate ion pairs have been synthesised. 4-Alkoxyphenylpentamethylguanidinium iodides were also prepared to determine the influence of congruently shaped anions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 41 publications
3
38
0
Order By: Relevance
“…The synthesis of guanidinium–sulfonimide ion pairs commenced with the commercially available sulfonyl chloride 4 [38], which was treated with trifluoromethanesulfonamide ( 5a ) in the presence of NEt 3 following a procedure by Hesemann and Brunel [40]. Then the fluorinated sulfonimide was converted to the potassium salt 6a after recrystallization from MeOH in 60% yield (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of guanidinium–sulfonimide ion pairs commenced with the commercially available sulfonyl chloride 4 [38], which was treated with trifluoromethanesulfonamide ( 5a ) in the presence of NEt 3 following a procedure by Hesemann and Brunel [40]. Then the fluorinated sulfonimide was converted to the potassium salt 6a after recrystallization from MeOH in 60% yield (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…Sulfonimides, which are directly bound to a mesogenic group, have not been described until now. We have recently described the concept of complementary ion pairs, where guanidinium sulfonate 1 with both mesogenic cation and anion displayed improved mesophase stability and increased phase widths as compared to their counterparts bearing a nonmesogenic spherical halide counterion [3839] (Scheme 1). …”
Section: Introductionmentioning
confidence: 99%
“…Hence, the influence of chain lengths, type of head group and counterion on the mesomorphic properties of ILCs has been investigated by several groups. [2][3][4]17,18] Furthermore, recent work by Tschierske, Cheng [19,20] and Laschat [21] has shown that by increasing the number of alkyloxy side chains on the same mesogenic unit the whole range of mesophase types from smectic A (SmA) to columnar (Col) and even cubic (Cub) could be obtained from structurally similar compounds. The effect of bending of the mesogenic core, however, has been explored much less, although it is well known from typical organic crystals (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Previous work on guanidinium sulphonates demonstrated that congruent ion pairs − in which the spherical counterion in classical ILCs is replaced by a mesogenic counterion of similar shape as compared to the mesogenic cation − allow tailoring of the transition temperatures and mesophase range to some extent. [17] We were thus curious whether congruent ion pairs with a bent cation and both spherical and congruent anions would simply affect the transition temperatures or even lead to different mesophase types. The results were compared to the linear congruent ion pairs where with both para-substituted 4-alkoxyaryl guanidinium cations and 4-alkoxyaryl sulphonate anions SmA phases were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…at present, 7−17 which provide some theoretical basis for the structure analysis of ILs, the design and synthesis of novel functionalized ILs. 18,19 In addition, ILs have better solubility and surface activity; thus, they have been widely used in many scientific fields. 20−27 However, studies on the surface tension and solubility of ILs are still scarce, and the surface tensions of only a few of ILs have been reported; 28−32 Previous studies mainly have been done on the qualitative analysis of the solubility of ILs in organic or inorganic solvents, with little attention paid to the quantitative analysis of their solubility and the general law of solubility; The surface tension and solubility for most common ILs mainly concentrates on several N-alkyl-N-methylimidazolium ILs.…”
mentioning
confidence: 99%